METODE PEMBINAAN PENDIDIKAN KARAKTER PADA MASA PANDEMI COVID-19 DI MTs MUHAMMADIYAH 07 KLEGO BOYOLALI - Vironika Kumalasari; Nurul Latifatul Inayati (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2020)
It is increasingly seen that the character of today's children is getting worse and worse due to environmental impacts, technological advances, and the lack of parental roles in cultivating good children's character. And also due to their lack of knowledge and appreciation in religion that is obtained at school. So character education is very important to be implemented even though at this time during the Covid-19 pandemic. MTs Muhammadiyah 07 Klego Boyolali is an Islamic school that has implemented a character education program since it was first established. MTs Muhammadiyah 07 Klego Boyolali during the covid-19 pandemic also continues to apply character education development to its students online with several methods carried out by the school. This study aims to (1) describe the implementation of the method of character education development during the Covid-19 pandemic at Mts Muhammadiyah 07 Klego Boyolali, (2) describe the obstacles in applying the method of character education development during the Covid-19 pandemic at Mts Muhammadiyah 07 Klego Boyolali.The research is qualitative, taking the place and subject of the research at MTs Muhammadiyah 07 Klego Boyolali. Data collection was done by interview, observation, and documentation. Meanwhile, data analysis was carried out with three data reduction events, data display, and conclusion drawing or data verification. To ensure the validity of the data obtained, this is done by triangulation of sources and triangulation of techniques.Based on the data analysis carried out, it can be concluded that the method of character education development during the covid-19 pandemic at MTs Muhammadiyah 07 Klego Boyolali is by using the habituation method. That is by using activity books/communication books given to students to monitor student activities at home such as character habits that students usually do at school. This communication book consists of two activities, namely activities at home and activities at school. In implementing the program of character education development methods in schools, MTs Muhammadiyah 07 Klego Boyolali has the aim of facilitating the process of continuously improving the character of students and training themselves for the realization of better student character. To evaluate the results of the character education development program in schools during the COVID-19 pandemic, using the home visit method. This home visit is carried out if students experience internal family problems, behavior problems in Madrasas, and problems related to learning in the form of attendance at Madrasas. Obstacles in Applying Character Education Guidance Methods During the Covid-19 Pandemic Period at MTs Muhammadiyah 07 Klego Boyolali are internal and external factors. Internal factors are the constraints in the form of limited student facilities (such as cellphones, quotas, and networks). Constraints from external factors are (1) Lack of teacher cohesiveness, (2) Lack of school facilities, (3) Schools cannot directly monitor the process of character building/distance constraints, (4) Parents are busy working, (5) Parents are less than optimal in supervising children, (6) parents are indifferent to the program/behavior of children at school, (7) the influence of the community environment is not good.